NOTES ON INTESTINAL PARASITIC DISEASES IN ARTISANAL FISHERMEN OF THE FISHING TERMINAL OF CHORRILLOS (LIMA, PERU) - Zelada Castro, Henry (2013)
A fecal parasitological study of the population performing artisanal fishing of Terminal Pesquero de Chorrillos (Fishing Terminal of Chorrillos), Province of Lima, Peru, was conducted aiming at determining the prevalence of endoparasites and their relationship with fishing activity. Fecal samples were examined by the Ritchie's Method and the Spontaneous Sedimentation in Tube Technique. The prevalence of endoparasites was 68%. The only pathogenic protozoa found was Giardia intestinalis (syn. G. lamblia) (Lambl, 1859) Kofoid & Christiansen, 1915 with a 16% prevalence. The helminth parasites found included Hymenolepis nana (Culbertson, 1940) and Ascaris lumbricoides (Linnaeus, 1758), both with a 4% prevalence. Commensal parasites found included Endolimax nana (Wenyon & O´Connor, 1917) at a prevalence reaching 40%, followed by Entamoeba coli (Grassi, 1879) with 28% and finally Iodamoeba butschlii (Prowazek, 1911) with 4%, it is recommended to implement health education strategies and a permanent monitoring.